Combinations of bio-active dietary constituents affect human white adipocyte function in-vitro. Issue 1 (December 2016) - Warnke, Ines; Jocken, Johan; Schoop, Rotraut; Toepfer, Christine; Goralczyk, Regina; Schwager, Joseph
Abstract Background Specific bio-active dietary compounds modulate numerous metabolic processes in adipose tissue (AT), including pre-adipocyte proliferation and differentiation. AT dysfunction, rather than an increased fat massper se, is strongly associated with the development of insulin resistance and is characterized by impaired adipogenesis, hypertrophic adipocytes, inflammation, and impairments in substrate metabolism. A better understanding of mechanisms underlying AT dysfunction may provide new strategies for the treatment of obesity-associated metabolic diseases. Here we evaluated the role of (all-E)-lycopene (Lyc), eicosapentaenoic acid (EPA) ortrans -resveratrol (Res) and combinations thereof on human white adipocyte function. Methods In-vitro differentiating human pre-adipocytes were treated with EPA, Lyc and Res or their combinations for 14 days. The effects on intracellular lipid droplet (LD) accumulation, secreted anti- and pro-inflammatory cyto-/adipokines (e.g. adiponectin, IL-6, IL-8/CXCL-8 and MCP-1/CCL2) and on gene expression of markers of adipocyte differentiation and substrate metabolism (e.g. PPAR-gamma, C/EBP-alpha, GLUT-4, FAS, ATGL, HSL, and PLIN-1) were measured by fluorescent microscopy (Cellomics™), multi-parametric LiquiChip® technology and quantitative RT-PCR, respectively. Results Treatment of differentiating adipocytes for 14 days with the combination of Lyc/Res and EPA/Res resulted in significantly inhibited LD formation ( -25 and -20%, respectively) compared to the effects of the single compounds. These morphological changes were accompanied by increased mRNA levels of the adipogenic marker PPAR-gamma and the lipase ATGL and by decreased expression levels of lipogenic markers (LPL, FAS, GLUT-4) and the LD-covering protein PLIN-1. In addition, a blunted adipocyte secretion of pro-inflammatory cytokines (IL-6 and MCP-1) and adiponectin was observed following treatment with these compounds. Conclusion The combination of the dietary bio-actives Lyc and EPA with Res might influence adipocyte function by affecting the balance between adipogenic, lipogenic and lipolytic gene expression, resulting in a reduced LD storage and a less inflammatory secretion profile. Taken together, our results indicate that combinations of dietary compounds may be beneficial for the prevention and treatment of metabolic disorders via effects on human white adipocyte function.